Key Actors in DKI Jakarta Entrepreneurial Development Model With The Intrepretative Structural Modeling (ISM) Approach - Asep Taryana; Mukhamad Najib; Harianto; Bustanul Arifin (Indonesian Journal of Business and Entrepreneurship (IJBE), 2021)
Entrepreneurship is faced with the challenges of environmental dynamics in the TUNA era (Turbulence, Uncertainty, Novelty, and Ambiguity). This paper aims to analyze entrepreneurship development models in DKI Jakarta. The data used in this study are primary and secondary data. This study uses a method with an analytical approach, Interpretative Structural Modeling (ISM). The elements and sub-elements in the ISM questionnaire were obtained from discussions with experts, including local government, entrepreneurs, academics, and the community. The output of ISM analysis is the sub-elements' positions in the four quadrants of the diagram and the level structuring based on the follow-up priority. This study found that sub-elements comprised of bank financial institutions (Bank DKI), LPDB, entrepreneurial empowerment volunteers, universities (LPPM), and researchers (lecturers) were included in sector II (dependent). Other sub-elements like DPRD, kasatpel, the business community, non-bank financial institutions, entrepreneurial activists, influential figures, and the public were included in sector III (linkage). There are sub-elements in sector IV (independent), such as governors, mayors/regents, related agencies, business actors, e-commerce, online media, and endorsers. The ISM analysis results show that the sub actor with the highest influence level is the governor. It shows that the governor has a very strategic role in developing entrepreneurship in DKI Jakarta. Keywords: entrepreneur, ISM, entrepreneurship development model, developing entrepreneurship